Erythropoietin; bright future and new hopes for an old drug - Mehri Kadkhodaee (Society of Diabetic Nephropathy Prevention, 2012)
Recent publications have suggested renoprotective actions for erythropoietin in certain models of acute kidney injury. In a study by Rafieian-Kopaei et al., the effects of erythropoietin on amelioration of gentamicin-induced renal toxicity was investigated and renoprotective effect for Eprex, an analogue of erythropoietin was shown when the drug was given in combination with gentamicin. There has also been a protective effect when the drug was applied after gentamicin administration. Thus, the drug was effective even after induction of tubular damage which opens a very valuable window for its therapeutic actions. However, there are still needs for studies on the mechanisms which are involved in these protective actions